Effect Of Antibacterial Gel Of Bidara Leaf Extract For Episiotomy Wound Healing At Hams Rsu, 2021 - Indriati Aulia; Ririn Angraini (Institute of Computer Science (IOCS), 2021)
Wounds to the perineum or episiotomy are difficult to keep clean and dry. Special observations andcare are needed to ensure the perineal part can heal quickly and inspections should be carried out to find out if there are signs of infection or inflammation of the part. One of the medicinal plants that have the potential to treat wounds is the Bidara plant (Ziziphus Mauritiana). The Bidara plant (Ziziphus Mauritiana) is a plant that has many properties and has been used for herbal medicine in several countries and has been clinically investigated for its content such as the content of alkaloid compounds, glycosides, saponins, flavonoids, tertenoids and phenolics as well as the most abundant antioxidant activity in the leaves. .This research is a quantitative research using pre-experimental or quasi method. This study was conducted to determine the effect of using antibacterial gel of bidara leaf extract on episiotomy wound healing in the working area of HAMS KISARAN RSU. Based on the results of statistical tests using the Wilcoxon test, it is known that the p value (0.005) < (0.05) means Ho is rejected, so there are differences in episiotomy wound healing before and after the use of antibacterial gel of bidara leaf extract. These results prove that there is a significant effect of using antibacterial gel of bidara leaf extract on episiotomy wound healing at HAMS Hospital Kisaran. These results prove that the use of antibacterial gel of bidara leaf extract is effective in accelerating episiotomy wound healing.